2020
DOI: 10.1016/j.heliyon.2020.e03577
|View full text |Cite
|
Sign up to set email alerts
|

The effect of platelet-rich plasma on the achievement of pregnancy during frozen embryo transfer in women with a history of failed implantation

Abstract: The aim of this study was to evaluate the effect of platelet-rich plasma (PRP) on the rate of implantation and pregnancy in women with repeated failed implantation during frozen embryo transfer. Methods: This study was conducted on 50 infertile women candidates (who were referred to the Infertility Treatment Center of Besat Hospital in Sanandaj) with a history of failed implantation for the purpose of frozen embryo transfer. The participants were randomly divided into two groups (n ¼ 25). In the first group (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 44 publications
0
32
0
1
Order By: Relevance
“…However, contradictory views on the usefulness of PRP perfusion treatment in IVF reproductive medicine persists. Tehraninejad and Allahveisi found that the pregnancy outcomes, namely, the clinical and ongoing pregnancy rates, live birth rates were similar between the PRP intrauterine infusion group and the control group in RIF patients of FET cycles ( 10 , 11 ). The reason for the inconsistency between our results and those of others might be attributable to the different subject cohorts, different definitions of RIF and wide variety of PRP preparation protocols.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…However, contradictory views on the usefulness of PRP perfusion treatment in IVF reproductive medicine persists. Tehraninejad and Allahveisi found that the pregnancy outcomes, namely, the clinical and ongoing pregnancy rates, live birth rates were similar between the PRP intrauterine infusion group and the control group in RIF patients of FET cycles ( 10 , 11 ). The reason for the inconsistency between our results and those of others might be attributable to the different subject cohorts, different definitions of RIF and wide variety of PRP preparation protocols.…”
Section: Discussionmentioning
confidence: 90%
“…To date, only a few RCT studies on intrauterine infusion of PRP have been performed in the reproductive field. Eftekhar and Nazari suggested that PRP could expand the thin endometrium and improve clinical pregnancy outcomes ( 17 , 20 ), while Allahveisi's study concluded that intrauterine infusion of PRP did not improve pregnancy outcomes in patients with recurrent implantation failure ( 11 ). Design of placebo in the control group was inconsistent across studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In infertile women with a history of failed implantation, intrauterine PRP infusion before frozen ET was found to have no significant effect on pregnancy [16]. A prospective cohort with a large number of patients is necessary to explore the underlying mechanisms responsible for PRP's beneficial effects and further investigate the benefits of PRP treatment in women with a thin endometrium who have undergone frozen ET (FET).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, implantation is a very complicated process regulated by a number of complex molecules such as hormones, cytokines, and growth factors which play together to induce endometrial receptivity for embryo at blastocyst stage [18]. Growing data show that PRP infusion is an effective approach for the improvement of pregnancy outcomes in the patients undergoing IVF/ICSI cycles, mostly in women who were not able to respond to the standard treatment [12,19,20]. Since various studies have demonstrated that the expression of growth factors in the endometrium of women with RIF is less than normal fertile women, local infusion of PRP which contains several growth factors and cytokines may improve endometrial receptivity and embryo implantation [18,21].…”
Section: Discussionmentioning
confidence: 99%